Timing of Alemtuzumab With Respect to Day of Bone Marrow Infusion and its Effects Upon Engraftment and Graft-Versus-Host Disease in Patients With Sickle Cell Disease: A Single-Institutional Study. Issue 8 (November 2020) - Sahdev, Indira; Brochstein, Joel; Werther, Nan; Stiles, Jessica
Abstract : The possible impact of "late" alemtuzumab (administered on days −10 to −8) versus "early" alemtuzumab (−19 to −17) with respect to engraftment and acute/chronic graft-versus-host disease (GvHD) in a group of 25 pediatric patients with sickle cell disease undergoing bone marrow transplantation following conditioning with alemtuzumab, fludarabine, and melphalan is reported. The first 9 patients received "late" alemtuzumab followed by bone marrow transplantation from HLA-matched sibling donors. The next 16 patients undergoing matched sibling transplants received "early" alemtuzumab. In the "late" group, 1 patient (11%) developed acute GvHD. Six patients (67%) achieved sustained engraftment. Three patients (33%) experienced graft rejection, leading to termination of enrollment of patients on this regimen. In the "early" alemtuzumab group, acute and chronic GvHD developed in 43% and 25% patients, respectively. None of the patients experienced graft rejection in this group of patients. Three patients developed stable mixed chimerism and 13 patients demonstrated 100% donor chimerism at 1 year post-transplant and beyond. These results suggest a benefit with respect to engraftment of administering "early" versus "late" alemtuzumab in this reduced-intensity conditioning regimen, however, with the possible cost of an increase in acute, and possibly chronic GvHD.